Water security and groundwater - Foster, S.; Villholth, Karen G.; Scanlon, B.; Xu, Y. (2021)
the concept of water security clarifies how water-resource scarcity impacts at varying geographic scales and on different socio-economic sectors, causing allocation conflicts and environmental risks • the large natural storage of most groundwater systems offers exceptional drought resilience and is well positioned to enhance water security for a wide range of water users • to perform this role sustainably groundwater systems require better data and analyses to inform water resource administration and effective pollution protection